Menyikapi Perasaan Insecure dan Overthinking dalam Perspektif Al-Quran - Pratama, Vemas Satria Edy; Rizaldi, Muhammad Rafi (Al-Wasathiyah: Journal of Islamic Studies, 2024)
Generation Z faces complex challenges, including mental health issues such as insecurity and overthinking. Both affect the quality of life, causing stress, anxiety, and depression. The digital era and social media reinforce this phenomenon. This study explores the level of insecurity and overthinking among generation Z and their causes, including the influence of environment and social media. A quantitative method was used with a questionnaire to 152 respondents of gen Z. The objectives also include the perspective of the Quran on insecurity and overthinking. The results show that the majority of respondents are teenagers, many of whom understand insecurity and overthinking. The objects of insecurity involve achievement in career, physical appearance, wealth, and relationships. Social media plays a role in fostering insecurity. The respondents generally take positive steps to overcome the problem, including getting closer to God. The concepts in the Quran, such as gratitude, destiny, and trust, provide a perspective that helps to overcome insecurity and overthinking. This study is expected to contribute to science and social welfare by integrating psychological, religious, and environmental aspects.